Illocutionary Acts Used by Indonesian Athletes in Instagram Caption in Asian Games 2018 - Batubara, Nisa Anggraini; Deliana, Deliana; Purba, Parlindungan (Universitas Negeri Semarang, 2020)
This research aims to describe the types of illocutionary acts used by Indonesian athletes in Instagram caption in Asian Games 2018, and to find out the type of illocutionary acts which is mostly used by the Indonesian athletes. This research used descriptive qualitative method. The source of data is the Instagram accounts used by Indonesian Asian Games Athletes. The data are in the form of Indonesian athletes’ 24 written utterances and categorized into types of illocutionary act based on Yule’s theory. Based on data analysis, the finding shows there are four types of illocutionary acts used by Indonesian athletes in Instagram caption in Asian Games 2018, namely representatives (14), expressives (7), directives (2), and commissive (1). Representative is mostly used by Indonesian athlete in Instagram caption in Asian Games 2018.